The impact of adult behavioural weight management interventions on mental health: A systematic review and meta‐analysis. (25th October 2020) - Jones, Rebecca A.; Lawlor, Emma R.; Birch, Jack M.; Patel, Manal I.; Werneck, André O.; Hoare, Erin; Griffin, Simon J.; van Sluijs, Esther M.F.; Sharp, Stephen J.; Ahern, Amy L.
Summary: There is good evidence that behavioural weight management interventions improve physical health; however, the impact on mental health remains unclear. We evaluated the impact of behavioural weight management interventions on mental health‐related outcomes in adults with overweight or obesity at intervention‐end and 12 months from baseline. Eligible studies were randomized controlled trials (RCTs) or cluster RCTs of adult behavioural weight loss interventions reporting affect, anxiety, binge eating, body image, depression, emotional eating, quality of life, self‐esteem and stress. We searched seven databases from inception to 7 May 2019 and included 43 articles reporting 42 RCTs. Eighteen studies were deemed to be at high risk of bias. We conducted random‐effects meta‐analyses, stratified analyses and meta‐regression using Stata. Interventions generated greater improvements than comparators for depression, mental health‐related quality of life and self‐efficacy at intervention‐end and 12 months from baseline. There was no difference between groups for anxiety, overall quality of life, self‐esteem or stress at intervention‐end. There was insufficient evidence to assess the impact on anxiety, binge eating, body image, emotional eating, affect, life satisfaction, self‐esteem or stress at intervention‐end and/or 12 months from baseline. Although evidence suggests that interventions benefit some aspects of mental health, high‐quality, transparently reported RCTs measuring a range of mental health outcomes over longer durations are required to strengthen the evidence base.